Synthesis Characterization Biological Activity of Heterocyclic Compounds: Synthesis, Characterization, and Biological Activity of Heterocyclic Compounds (Journal of Advances and Scholarly Researches in Allied Education, 2022)
To get Schiff bases derivatives malonic acid di hydrazide was reacted with CS2 KOH, followedby hydrazine hydrate. This produced 1,2,4-triazole, which was then reacted with various substitutedbenzaldehydes. Thiazolidines were produced via the reaction of Schiff bases with thioglycolic acid. Asimilar reaction between Schiff bases and glycine yielded imidazolidinone. FT-IR, 1 H-NMR, Uvvis spectra,melting temperatures, and T.L.C. purity checks were used to describe the compounds. Antibacterialactivity was tested on a subset of the produced compounds.